2019
DOI: 10.3390/toxins11040196
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Five Mycotoxins in Different Food Matrices in the Malaysian Market by Using Validated Liquid Chromatography Electrospray Ionization Triple Quadrupole Mass Spectrometry

Abstract: Mycotoxins are common food contaminants which cause poisoning and severe health risks to humans and animals. The present study applied chemometric approach in liquid chromatography-tandem mass spectrometry (LC-MS/MS) optimization for simultaneous determination of mycotoxins, i.e., aflatoxins B1, B2, G1, and G2, and ochratoxin A. The validated quick, easy, cheap, effective, rugged, and safe (QuEChERS)-LC-MS/MS method was used to study the occurrence of mycotoxins in 120 food matrices. The recovery ranges from 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…The highest AFG 1 concentrations in different spices have been reported in paprika (318.1 µg/kg) in Italy [ 107 ], anise (157.5 µg/kg), thyme (41.2 µg/kg), black pepper (31.5 µg/kg), rosemary (12.9 µg/kg), mustard (10.5 µg/kg) and parsley (8.1 µg/kg) in Egypt [ 109 ], and chili (7.0 µg/kg) in Malaysia [ 114 ].…”
Section: Mycotoxins and Microfungi In Spices From The Perspective mentioning
confidence: 99%
“…The highest AFG 1 concentrations in different spices have been reported in paprika (318.1 µg/kg) in Italy [ 107 ], anise (157.5 µg/kg), thyme (41.2 µg/kg), black pepper (31.5 µg/kg), rosemary (12.9 µg/kg), mustard (10.5 µg/kg) and parsley (8.1 µg/kg) in Egypt [ 109 ], and chili (7.0 µg/kg) in Malaysia [ 114 ].…”
Section: Mycotoxins and Microfungi In Spices From The Perspective mentioning
confidence: 99%
“…All of the target analytes were found to be more sensitive in the positive mode. Previous studies have demonstrated that most mycotoxins are likely to produce [M+H] + [ 16 , 27 , 28 , 29 , 30 , 31 ]. Full scan MS/MS was performed to examine the fragmentation of all target analytes.…”
Section: Resultsmentioning
confidence: 99%
“…Various methods have been employed for the determination of mycotoxins, including high-performance liquid chromatography (HPLC), gas chromatography-mass spectrometry (GC-MS), and enzyme-linked immunosorbent assay (ELISA) [ 10 ]. Additionally, liquid chromatography-tandem mass spectrometry (LC-MS/MS) has been widely used in the determination of mycotoxins in various complex matrices due to its high sensitivity and ability to detect multiple mycotoxins in a single analysis [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. LC-MS/MS is the most promising instrumental method for multi-mycotoxin determination.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports on dried grapes addressed mycotoxins and the relevant producer fungi, with most of them referring to OTA [51,52]. However, other mycotoxins were also studied, such as AFBs [53,54], FBs [55,56], Alternaria spp. mycotoxins, and others produced by Penicillium spp., such as mycophenolic acid [57], PAT [58], and CIT [59].…”
Section: Mycotoxins In the Grape Food Chainmentioning
confidence: 99%